The Concepts and Methods of Shaping Traditional and Virtual Relationships of Bank Employees with Clients - Michałowska , Mariola; Stankiewicz , Dariusz; Danielak, Wiesław (Studia Oeconomica Posnaniensia, 2018)
In practice, banks use different concepts and methods that support the formation of valuable and long-term relationships between a bank employee and clients. The study presents selected concepts and methods aimed at improving and developing both traditional and virtual customer relationships. With regard to the concept of relations, the determinants of shaping inter-organizational relations are been shown, with particular emphasis on the role of relational abilities and competences as well as relational capital.